Designing and optimizing digital circuit using FPSGA and DH - Kamil K.; Chong K.H.; Raveendran S.K. (2023)
This paper is presents the analysis of designing and optimizing digital circuit structure using Finite Persisting Sphere Genetic Algorithm (FPSGA) and (Double Helix) DH representation. The design is involved 4 Input and 1 Output of digital circuit with 6 min terms. The resulted circuit is verified using XILINX ISE Design Suite 13.2. The result obtained shows that the circuit is function and able to operate with minimum number of gates. 2013 IEEE.